Methods of architectural design for reconstruction of the hotels built on standart projects in the 1960-80s in ukraine - Bridnia, Larysa (B&M Publishing, 2015)
The issues of reconstruction of hotels, built on standard projects in Ukraine are being analyzed. The methods of functional and spatial transformation of these hotels based on the analysis of the main socio-economic, urban development, climatic and technical factors, combined with comprehensive analysis of their functional and space-planning structure are suggested. The main components of the feasibility and effectiveness of this methodology of reconstruction of these objects are being identified.
Keywords: architecture; reconstruction; reconstruction methods; hotels; typical hotel projects